Effects of non-invasive brain stimulation on walking and balance ability in Parkinson’s patients: A systematic review and meta-analysis - Zhang, Xinxin; Jing, Feiyue; Liu, Yu’ang; Tang, Jinyong; Hua, Xianfeng; Zhu, Jialin; Tuo, Haowen; Lin, Qihan; Gao, Pincao; Liu, Weiguo (Frontiers in Aging Neuroscience, 2023)
Objective: To investigate and contrast the effects of non-invasive brain stimulation (NIBS), including repeated transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), on walking and balance ability in patients with Parkinson’s disease(PD). Methods: The PubMed, Embase, Medline, Cochrane, CNKI, and Chinese WanFang databases were searched up to June 2022. Quality assessment was performed using the Cochrane Collaboration’s risk-of-bias guidelines, and the standardized mean differences(SMD) or mean differences (MD) for each outcome were calculated. Results: Among 32 eligible studies, including 1586 participants were analyzed in this meta-analysis. The results of the meta-analysis showed that NIBS was effective in improving UPDRS-III scores (MD = -2.07;95% CI, -2.62 to -1.53; P<0.00001; I2=6%) and variables associated with the ability of walk such as step width (SMD = 0.35; 95% CI, 0.16 to 0.55; P=0.0005; I2=38%), cadence (SMD = 0.3; 95% CI, 0.05 to 0.55; P=0.02; I2=25%), and 6MWT (MD = 62.86; 95% CI, 39.43 to 86.29; P<0.00001; I2=0%). In subgroup analyses across intervention types, UPDRS-III scores (rTMS: MD = -2.54; 95% CI, -3.16 to -1.92; P<0.00001; I2=0%; tDCS: MD = -1.20; 95% CI, -1.99 to -0.40; P=0.003; I2=0%) and TUGT time(rTMS: MD = -4.11; 95% CI, -4.74 to -3.47; P<0.00001; I2=0%; tDCS: MD = -0.84; 95% CI, -1.48 to -0.21; P=0.009; I2=0%) significantly improved. Moreover, our results also showed that compared to tDCS, rTMS was more significant in improving UPDRS-III scores and TUGT time(p＜0.05). Conclusion: NIBS benefits some walking ability variables but not balance ability in patients with PD. The rTMS significantly improved UPDRS-III scores and TUGT time compared to tDCS. Further studies are needed to determine the optimal protocol and to illuminate effects based on the ideal target brain regions, stimulation intensity, timing, and type of intervention. Systematic Review Registration: http://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022350782. Keywords: Non-invasive brain stimulation; Repetitive transcranial magnetic stimulation; Transcranial direct current stimulation; Parkinson’s disease; Meta-analysis.